2022
DOI: 10.1063/5.0105164
|View full text |Cite
|
Sign up to set email alerts
|

On-chip optical comb sources

Abstract: On-chip integration of optical comb sources is crucial in enabling their widespread use. Integrated photonic devices that can be mass-manufactured in semiconductor processing facilities offer a solution for the realization of miniaturized, robust, low-cost, and energy-efficient comb sources. Here, we review the state of the art in on-chip comb sources, their applications, and anticipated developments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 334 publications
0
10
0
Order By: Relevance
“…So Si3N4 MRR is employed as the external cavity in our experiment. To miniaturize the device, the semiconductor laser is integrated with a photonic circuit in three different methods: monolithic integration, heterogeneous integration and hybrid integration 5 . Compared to the former two methods, the third method has the advantage of improving the performance of the III-V chip and passive chips separately 6 .…”
Section: Introductionmentioning
confidence: 99%
“…So Si3N4 MRR is employed as the external cavity in our experiment. To miniaturize the device, the semiconductor laser is integrated with a photonic circuit in three different methods: monolithic integration, heterogeneous integration and hybrid integration 5 . Compared to the former two methods, the third method has the advantage of improving the performance of the III-V chip and passive chips separately 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 provides an overview of the lowest repetition rates to date for integrated mode-locked diode lasers based on standard (AM) mode-locking techniques [56,63,65,140,[169][170][171][172][173][174][175][176], adapted from the overviews provided in Ref. [63] and [177].…”
Section: The Problem Of High Loss In Diode Lasersmentioning
confidence: 99%
“…It is important to note that for comb generation, also alternatives to standard diode laser mode-locking have been reported that enable lower repetition rates (an extensive review is provided by Ref. [177]). For instance, using a 3.55 GHz mode-locked laser, a very low repetition rate of 55 MHz was realized via pulsepicking based on an on-chip Mach-Zehnder modulator [52].…”
Section: The Problem Of High Loss In Diode Lasersmentioning
confidence: 99%
See 2 more Smart Citations